Carbon materials for analytical electrochemistry: printed carbon materials and composites. (August 2015) - Sharp, D.; Burkitt, R.
Abstract : Carbon based materials have a wel-founded history in electroanalytical science, and over the previous 55 years have offered many developments in terms of form, properties and modifications that can modulate the electrochemical properties. This review explores some of the more recent developments in carbon materials focussing on the versatility of graphitic carbon, its modification and a summative overview of the use of printing methodologies to fabricate electrodes and sensors based on modified carbon inks. A range of printed carbon electrodes and biosensors are discussed, based on the incorporation of electrocatalyst, mediator, modifier or enzyme, directly into the ink, to offer sensitive detection mechanisms. Future possibilities and strategies are discussed to explore ways in which printed carbon composites may be benefit electrochemistry and provide an emerging basis for cost effective detection technologies that are easily translated from research into commercial use.